Regional Language Studies. Newfoundland, Number 21 (15 April 2009) - Pope, Peter Edward, 1946; Woodrow, Maureen; Smith, Derek; Nichol, Donald W.; Seary, E. R. (Memorial University of Newfoundland. Department of English Language and Literature, 2009)
French place name survivals on Newfoundland's Petit Nord : Crouse Fischot and Les Ilettes / Peter E. Pope -- Research notes : community-based mapping on Change Island / Maureen Woodrow and Derek Smith -- Added early French names on the Western shore of Placentia Bay / William J. Kirwin -- "Scum of the earth", and "which nobody can deny" and other verbal felicities from The New Foundling Hospital for Wit / Donald W. Nichol -- From the Archives: Proposals for developments in research and tuition in the Department of English (1955) / E. R. Seary -- Miscellany: Collections in the English Language Research Centre. Corrections. Bibliography / William J. Kirwin -- Figure: Fishing stations on the Petit Nord.